2008
DOI: 10.1080/10520290802451085
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry in the evaluation of neovascularization in tumor xenografts

Abstract: Angiogenesis, or neovascularization, is known to play an important role in the neoplastic progression leading to metastasis. CD31 or Factor VIII-related antigen (F VIII RAg) immunohistochemistry (IHC), is widely used in experimental studies quantifing tumor neovascularization in immunocompromised animal models implanted with transformed human cell lines. Quantification, however, can be affected extensively by variations in the methodology used to measure vascularization including antibody selection, pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 29 publications
3
96
0
2
Order By: Relevance
“…This method allows quantification of angiogenesis through immunohistochemical detection of CD31 [48]. In this study, the expression of angiogenesis measured by CD31 staining was consistent with the RT-PCR findings.…”
Section: Discussionsupporting
confidence: 87%
“…This method allows quantification of angiogenesis through immunohistochemical detection of CD31 [48]. In this study, the expression of angiogenesis measured by CD31 staining was consistent with the RT-PCR findings.…”
Section: Discussionsupporting
confidence: 87%
“…Again one has to consider that heterogeneous methodologies used to calculate MVD among different studies might also play a role. In our study, we chose to highlight the tumor vessels with an antibody to CD31 because it has been shown that MVD is better assessed by CD31 (or CD34) than by factor VIII-related antigen [26,27], often used in other studies. In addition, we selected random areas of the tumor [5] with the help of computer software to minimize potential inter and intraobserver variability in selecting particular areas at the growing edge of the tumor or the most vascularized ''hot spot'' areas.…”
Section: Discussionmentioning
confidence: 99%
“…Four micron serial sections were deparaffinized and rehydrated through graded ethanol and rinsed in distilled water. Antigen retrieval was carried out by the autoclave method (120 8C) for 3 min in 0.5 M Tris buffer at pH 10 (for CD31; Wang et al 2008) or 0.01 M citrate buffer at pH 6.0 (for Ki67, VEGFR2 and DRD2) followed by cooling for 20 min at room temperature. Sections were gently rinsed in deionized water and then transferred to a 0.5 M Tris-based solution in 0.15 M NaCl with 0.1% v/v Triton-X-100 at pH 7.6 (TBST).…”
Section: Immunohistochemistrymentioning
confidence: 99%